Systematic review and meta-analysis of endoscopic submucosal dissection vs endoscopic mucosal resection for colorectal lesions. Issue 1 (February 2016) - Arezzo, Alberto; Passera, Roberto; Marchese, Nicola; Galloro, Giuseppe; Manta, Raffaele; Cirocchi, Roberto
Background and aims: This systematic review and meta-analysis compares the safety and effectiveness of endoscopic submucosal dissection (ESD) and endoscopic mucosal resection (EMR) in the treatment of flat and sessile colorectal lesions >20 mm preoperatively assessed as noninvasive. Methods: We reviewed the literature published between January 2000 and March 2014. Pooled estimates of the proportion of patients with en bloc, R0 resection, complications, recurrence, and need for further treatment were compared in a meta-analysis using fixed and random effects. Results: A total of 11 studies and 4678 patients were included. The en bloc resection rate was 89.9% for ESD vs 34.9% for EMR patients (RR 1.93 p  < 0.001). The R0 resection rate was 79.6% for ESD vs 36.2% for EMR patients (RR 2.01 p  < 0.001). The rate of perforation was 4.9% for the ESD group and 0.9% for EMR (RR 3.19, p  < 0.001), while the rate of bleeding was 1.9% for ESD and 2.9% for EMR (RR 0.68, p  = 0.070). Therefore, the overall need for further surgery, including surgery for oncologic reasons and surgery for complications, was 7.8% for ESD and 3.0% for EMR (RR 2.40, p  < 0.001). Conclusions: ESD achieves a higher rate of en bloc and R0 resection compared to EMR, at the cost of a higher risk of complications. This, added to an increased need for surgery for oncologic reasons for a plausible tendency to extend indication for endoscopic excision, increases the risk of further surgery after ESD.